2022
DOI: 10.1186/s13148-022-01368-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased copy number of imprinted genes in the chromosomal region 20q11-q13.32 is associated with resistance to antitumor agents in cancer cell lines

Abstract: Background Parent of origin-specific allelic expression of imprinted genes is epigenetically controlled. In cancer, imprinted genes undergo both genomic and epigenomic alterations, including frequent copy number changes. We investigated whether copy number loss or gain of imprinted genes in cancer cell lines is associated with response to chemotherapy treatment. Results We analyzed 198 human imprinted genes including protein-coding genes and noncod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 163 publications
0
1
0
Order By: Relevance
“…NRXN3 was shown to be associated with tumor aggressiveness in studies of gliomas and glioblastoma patients with high NRXN3 expression were found to have a poor prognosis [39] . By analyzing the Cancer Cell Line Encyclopedia (CCLE)-Genomics of Drug Sensitivity in Cancer (GDSC) dataset, Krushkal et al found a significant correlation between increased GNAS expression and tumor resistance to chemotherapeutic agents [40] . Furthermore, GNAS activation significantly promoted growth and progression in a mouse model of Small Cell Lung Cancer (SCLC) [41] .…”
Section: Resultsmentioning
confidence: 99%
“…NRXN3 was shown to be associated with tumor aggressiveness in studies of gliomas and glioblastoma patients with high NRXN3 expression were found to have a poor prognosis [39] . By analyzing the Cancer Cell Line Encyclopedia (CCLE)-Genomics of Drug Sensitivity in Cancer (GDSC) dataset, Krushkal et al found a significant correlation between increased GNAS expression and tumor resistance to chemotherapeutic agents [40] . Furthermore, GNAS activation significantly promoted growth and progression in a mouse model of Small Cell Lung Cancer (SCLC) [41] .…”
Section: Resultsmentioning
confidence: 99%